Perancangan User Experience Aplikasi Pelaporan Keluhan Masyarakat Menggunakan Metode Human-Centered Design - Aryun Nadaa Aniesiyah; Herman Tolle; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Public complaints reporting application for Malang city is an e-complaint application that utilizes GPS and geotagging technology. The application was developed to report various problems that occurred in various fields in Malang. User experience is an important factor for the success of e-complaint. This study aims to design the user experience for public complaints reporting application for Malang city. Evaluation using usability testing and User Experience Questionnaire (UEQ) is done to measure the user experience level and to know the problem about user experience from application design that has been built. Some of the problems are the menus that was not successfully found by users and user's incomprehension to use application features. After the initial evaluation is done then do redesign as solutions of user experience problems on the old design. The comparison of usability value of old application design and new design obtained significant difference that is equal to 48.98%. The comparison of UEQ benchmark scale also can be seen that the scale of attractiveness and perspicuity change from the category of â€œbadâ€ into â€œgoodâ€, on the scale of efficiency, dependability, and stimulation change from the category of â€œbadâ€ into â€œexcellentâ€, and on novelty scale change from the category â€œbelow averageâ€ into â€œexcellentâ€. Thus, it can be concluded that the design solution gives a more positive perception in terms of user experience and better in terms of usability.